Vrae na die verwantskap tussen wys begeerte en vakwetensk ap, met verwysing na opvoedkunde en sy vak filosofie - Schoeman, P. G. (Koers, 1989)
In this paper it is argued that the pursuit of all special sciences is always intimately interwoven with, and can in fact never be separated from, presuppositions which are essentially philosophical in nature. The peculiar nature of philosophy is investigated and the relationship between philosohpy and the various special sciences is indicated. From this survey it is concluded that particular philosophical presuppos it ions exert an a priori influence on the most concrete problems of any particular science. It thus becomes apparent that even education as a special area of scientific investigation can never be regarded as possessin g an essential autonomy with respect to philosophy in the sense of a theory of reality.